Salvage focal brachytherapy in castration‐resistant prostate cancer with neuroendocrine differentiation after radiation therapy - Takahiro Komori; Takeo Kosaka; Keitaro Watanabe; Tomoki Tanaka; Yota Yasumizu; Hiroshi Hongo; Shuji Mikami; Toshio Ohashi; Mototsugu Oya (IJU Case Reports, 2022)
Introduction Treatment strategy for castration‐resistant prostate cancer with neuroendocrine differentiation after radiation therapy has not been established. Case presentation We described a case of castration‐resistant prostate cancer with neuroendocrine differentiation after initial external beam radiotherapy followed by salvage androgen deprivation therapy. Magnetic resonance imaging detected recurrence of a suspicious lesion in the left lobe of the prostate, although the prostate‐specific antigen level was <0.2 ng/mL. Transperineal prostate saturation needle biopsy detected adenocarcinoma with neuroendocrine differentiation. The patient underwent salvage focal brachytherapy and had a prostate‐specific antigen progression‐free survival of 20 months with no obvious adverse events. No recurrence has been detected on magnetic resonance imaging for 18 months. Conclusion Salvage focal brachytherapy for prostate cancer after external beam radiotherapy can be one of the treatment strategies for local recurrence of castration‐resistant prostate cancer with neuroendocrine differentiation.